To solve the system by substitution, we will set the two expressions for y equal to each other and solve for x.
So we have:
-5x - 10 = -10x
Add 10x to both sides:
5x - 10 = 0
Add 10 to both sides:
5x = 10
Divide by 5:
x = 2
Now that we have found the value of x, we can substitute it back into either equation to solve for y. Let's use the second equation:
y = -10(2)
y = -20
Therefore, the solution to the system of equations is x = 2 and y = -20.
Solve the system by substitution.
y, equals, minus, 5, x, minus, 10
y=
−5x−10
y, equals, minus, 10, x
y=
−10x
1 answer